Use of metaphors about exome and whole genome sequencing. Issue 5 (29th January 2016) - Nelson, Sarah C.; Crouch, Julia M.; Bamshad, Michael J.; Tabor, Holly K.; Yu, Joon‐Ho
Abstract : Clinical and research uses of exome and whole genome sequencing (ES/WGS) are growing rapidly. An enhanced understanding of how individuals conceptualize and communicate about sequencing results is needed to ensure effective, mutual exchange of information between care providers and patients and between researchers and participants. Focus groups and interviews participants were recruited to discuss their attitudes and preferences for receiving hypothetical results from ES/WGS. African Americans were intentionally oversampled. We qualitatively analyzed participants' speech to identify unsolicited metaphorical language pertaining to genes and health, and grouped these occurrences into metaphorical concepts. Participants compared genetic information to physical objects including tools, weapons, contents of boxes, and formal documents or reports. These metaphorical concepts centered on several key themes, including locus of control; containment versus release of information; and desirability, usability, interpretability, and ownership of genetic results. Metaphorical language is often used intentionally or unintentionally in discussions about receiving results from ES/WGS in both clinical and research settings. Awareness of the use of metaphorical language and attention to its varied meanings facilitates effective communication about return of ES/WGS results. In turn, both should foster shared and informed decision‐making and improve the translation of genetic information by clinicians and researchers. © 2016 Wiley Periodicals, Inc.